Percursos na construção do conhecimento agroecológico - Gardim, Vanessa Gonçalves (2016)
The current investigation is set in the context of the resistance against the impositions of agribusiness and finds in the agroecological transition its object of study. Paths in the construction of agroecological knowledge from the farmers and articulators standpoint were analysed in the context of the consolidation of Agroecology Network Ecovida (Rede Ecovida de Agroecologia), in the north of Paraná. The aims of the study unfold the identification of: (i) farmers, (ii) their relation with the participatory method and diálogo de saberes (methodology of diffusion and construction of knowledge), (iii) their motivation to enter and stay in agroecological transition, (iv) the paths of individual and familiar signification of the social construction of knowledge on agroecology. The research was conducted in the metropolitan region of Londrina (state of Paraná, Brazil), in a context driven by initiatives of organic and agroecological production, involving farmers, technicians, consumers and academics, mediated by NEAGRO (Núcleo de EstudosemAgroecologia) a group of study in agroecology of the State University of Londrina. The methodology used is qualitative research, conducted through the dialectical method. Semistructured interviews with farmers and articulators were conducted through discourse analysis. Graphs of paths of construction of agroecological knowledge were illustrated and grouped in three profiles, identified as: ecological, market-oriented and militant. Through direct observation and analysis of interviews, the interactions experienced in the paths of knowledge were highlighted and characterised by the accounts shared in the interviews. Mapping the paths, defining the identity traces and affirming the importance of diálogo de saberes highlight the experiences of networks, groups, associations and cooperatives as (re)constructors of ecology, food sovereignty and farmers knowledge.